Science and Policy Interactions in Assessing and Managing Marine Ecosystems in the Southern Ocean - Press, Anthony J. (Frontiers in Ecology and Evolution, 2021)
Good policy can only be built and implemented using sound advice, and a clear understanding of risk. Scientific advice will often be qualified by the extent of research and knowledge, and uncertainties about the current and future state of the environment. Bodies tasked with protecting the Antarctic environment are required to make decisions based on the best available advice. To not take decisions in the absence of certainty is contrary to clear obligations to protect the Antarctic environment contained in the instruments of the Antarctic Treaty System. The risk of foreclosing future options to protect the environment by indecision is as great, if not greater, than making decisions with incomplete advice, and then actively managing that decision into the future. This “Perspective” explores the relationship between science and policy in the context of the Conference on Marine Ecosystem Assessment for the Southern Ocean held in 2018.